Preparation of Carrier-Free Inhalable Dry Powder of Rivaroxaban Using Two-Step Milling for Lung-Targeted Delivery - Young-Jin Kim; Jaewoon Son; Chang-Soo Han; Chun-Woong Park (Pharmaceutics)
Background/Objectives: This study aimed to develop a dry powder inhalation (DPI) formulation of rivaroxaban (RVX) using a combination of bead milling (BM) and jet milling (JM) to enhance lung-targeted delivery for the effective treatment of pulmonary embolism while minimizing systemic exposure. Methods: A carrier-free DPI formulation of RVX was developed using sequential BM and JM, with L-leucine incorporated at various concentrations (1%, 5%, and 10%) as a force control agent. The formulations were characterized for particle morphology, size distribution, crystallinity, and thermal properties. The in-vitro aerodynamic performance was evaluated using a next-generation impactor, while ex-vivo studies assessed anticoagulant activity. Pharmacokinetic and tissue distribution studies were carried out in Sprague Dawley rats following intratracheal administration, and the effects of inhaled RVX were compared with those of oral administration. Results: The optimized BM-JM-5L formulation achieved a Dv50 of 2.58 ± 0.01 µm and a fine particle fraction of 72.10 ± 2.46%, indicating suitability for pulmonary delivery. The two-step milling effectively reduced particle size and enhanced dispersibility without altering RVX’s physicochemical properties. Ex-vivo anticoagulation tests confirmed maintained or improved activity. In-vivo studies showed that pulmonary administration (5 mg/kg) led to a 493-fold increase in lung drug concentration and 2.56-fold higher relative bioavailability vs. oral dosing, with minimal heart tissue accumulation, confirming targeted lung delivery. Conclusions: The two-step milled RVX DPI formulations, particularly BM-JM-5L with 5% leucine, demonstrated significant potential for pulmonary administration by achieving high local drug concentrations, rapid onset, and improved bioavailability at lower doses. These findings highlight the feasibility of RVX as a DPI formulation for pulmonary delivery in treating pulmonary embolism.